ANALISIS KELENGKAPAN PRODUK DAN KUALITAS PELAYANAN PADA UD. SONIA KABUPATEN BIMA - Indra Widaryanto; Muhajirin Muhajirin; Ita Purnama (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This research investigates the level of product completeness and service quality at UD. Sonia, Bima Regency. A descriptive research method with a quantitative approach was employed, with a sample of 100 respondents who had previously shopped at UD. Sonia. The findings indicate that UD. Sonia's product completeness exceeds 75% of the expected criteria, indicating a good performance. However, the service quality falls short of the expected criteria, scoring less than 75%. This study recommends that UD. Sonia focus on improving its service quality to enhance customer satisfaction.